A Systematic Meta‐Analysis of the Effect of Interprofessional Education on Health Professions Students' Attitudes. Issue 12 (1st December 2019) - Wang, Zairan; Feng, Fenglian; Gao, Shang; Yang, Jiping
Abstract : Interprofessional education (IPE) is based on collaborative practices that increase the occasions for communication among those in various health professions. However, there is a paucity of literature about the effectiveness of IPE programs in health professions education. The aim of this systematic review and meta‐analysis was to objectively assess the literature on the effectiveness of IPE in improving health professions students' attitudes after training. The major scholarly databases were searched for relevant IPE studies involving predoctoral health professions students. Two independent researchers selected the studies, extracted the data, and assessed the quality of the studies. Meta‐analyses of the outcomes were performed using random effects models. Sixteen articles were ultimately selected for detailed review and meta‐analysis. The meta‐analysis showed that IPE training had a significant influence on students' understanding of collaboration and resulted in better attitudes about interprofessional teamwork. Subscale analysis showed that one subscale score (roles and responsibilities) did not statistically significantly improve after IPE training (p=0.06), whereas the other four subscale items showed statistically significant improvements (p<0.01). The test for overall effects showed that IPE training had a significantly positive influence on students' attitudes about IPE (Z=6.85, p<0.01). Subgroup results showed that medical students had more positive attitudes about IPE than did dental students. Regardless of profession, women students responded with significantly more positive feedback than did men students (p=0.02). These results suggest that intervention through IPE training has had positive effects in health professions education. Gender was an important factor impacting the outcomes of IPE. However, further clinical practice interventions may be helpful to enhance the IPE competence of health professions students.